Kinematic comparison of opencap and IMU with marker-based motion capture in treadmill running: a pilot study - Iskandar, M. N. S. I.; Teng, P. S. P. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The purpose of this pilot study was to compare lower-limb running kinematics measured using a markerless system, OpenCap, and inertial measurement units (IMUs) against the marker-based motion capture (mocap) system. One participant ran at 2.22 m/s on a treadmill for one minute. Mean absolute error (MAE) and root mean square error (RMSE) of hip, knee, and ankle flexion were calculated independently for all 3 devices. Time synchronization of devices was facilitated by performing a `kick` and identifying its peak knee angle prior to running. Offset correction was also applied to OpenCap and IMUs data to match those of marker-based mocap data at the start of time synchronization. OpenCap exhibited a higher degree of error than IMUs in all joint angles compared to marker-based mocap both before and after an offset correction was applied, with errors exceeding 10°.